2002
DOI: 10.17660/actahortic.2002.572.15
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Assisted Breeding for Disease Resistance in Lily

Abstract: The Asiatic hybrid lily ( Lilium L.) 'Connecticut King' harbours several beneficial traits such as partial resistance to Fusarium and complete resistance to tulip breaking virus (TBV). The variation in resistance to Fusarium was determined in four different greenhouse tests in four different years on the same 100 descendants of a backcross population. There was considerable variation in Fusarium resistance levels over the years. TBV resistance was determined and segregated, as expected, like a monogenic trait … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 14 publications
4
28
0
Order By: Relevance
“…The second population is an AA population of 100 individuals (Straathof et al. 1996, Van Heusden et al. 2002), which was produced in 1989.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second population is an AA population of 100 individuals (Straathof et al. 1996, Van Heusden et al. 2002), which was produced in 1989.…”
Section: Methodsmentioning
confidence: 99%
“…Four quantitative trait loci (QTL) for Fusarium resistance were identified whereas LMoV resistance was controlled by a single locus. Only the LG bearing the LMoV locus was published (Van Heusden et al. 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Abe et al (2002) reported the genetic analysis of floral anthocyanin pigmentation traits in Asiatic hybrid lilies using randomly amplified polymorphic DNA and inter-simple sequence repeat. Van Heusden et al (2002) used amplified fragment length polymorphism markers to map four quantitative trait loci (QTLs) for Fusarium oxysporum and a single locus of LMoV in an Asiatic backcross population. Shahin et al (2011) analyzed QTLs for several ornamental traits and disease resistance with amplified fragment length polymorphism, DArT, and fine-map NBS profiling.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the Fusariumresistant genes were recombined into the hybrids by crossing the cultivars of Lilium Asiatic with that of Llilium Oriental (Schenk, 1990;Barba-Gonzalez, 2005;Lim et al, 2000). However, the previous studies showed that the Fusarium resistance of lily was a multi-gene character (Heusden et al, 2002), and the identification of the resistant genes was rather complicated, besides the Fusarium-resistant genes of lily mainly existed in the Lilium Asiatic, which made it necessary to do the distant crosses between different groups of lily. All these resulted in a very low efficiency in breeding of resistant cultivars by gene introgression strategy …”
Section: Fusarium-resistant Mutant From Crosses Of Lilium Oriental Ofmentioning
confidence: 99%